Kualitas Air Sungai Walannae di Dusun Kampiri Desa Pallawarukka Kecamatan Pammana Kabupaten Wajo - Ranijintan, R.Puty; Hayat, A. M. Fadhil; Raodhah, Sitti (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
River is a stream of water on Earth's surface that is formed naturally from the land into the sea.Tha Water in Walannae river is a source of clean water in the community of Kampiri village of Pallawarukka districts in Pammana Wajo district. This study aims to determine the quality water of the river hamlet Kampiri Walannae in terms of parameters MPN Coliform, TSS (Total Suspended Solid), temperature, pH, BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand). This research was conducted by quantitative methods using descriptive observational approach to design through sampling at three points. That is the point I (Upstream), point II (middle) and point III (Downstream). Sampling was done by a combined technique (composite sample), which is in the morning (08:00 to 9:00) and afternoon (16:00 to 17:00). Some parameters (temperature and pH) performed in the field, while for the parameters (MPN Coliform) checked in Sengkang city Health Department Laboratory, and the parameters (TSS, BOD and COD) checked in Environmental Health Laboratory banta-Bantaeng. Parameter were based on the results of the examination for Coliform MPN highest yield at the third point on the afternoon of the 11000 (/ 100ml) and the lowest result at the third point on the morning of the 5400 (/ 100ml). Parameter TSS highest yield is on the afternoon of the third point of 105 (mg / l) and the lowest result at the point I am today is 62 (mg / l). Temperature measurement parameters morning point I, II, and III average 27C in the afternoon while I point 27̊Cdan points II and III point 29C, the difference temperature between the water and the air is still eligible under the deviation parameter is pH 3 was at its highest yield second morning at 8 and the lowest point of the first and the third morning ie 6. BOD highest yield at the third point of the afternoon of 36 (mg / l) and the lowest result at the first point on the afternoon of the 9 (mg / l). COD parameters the highest yield at the point II on the afternoon of the 42 (mg / l) and the lowest result at the point I on the morning of 23 (mg / l). Based on water quality standards according to the provincial governor SK Sul-Sel 69 Year 2010 on Standards of quality and criteria for environmental damage, for the parameters pH and temperature is still eligible, whereas for the parameter MPN Coliform, TSS, BOD and COD are not eligible. Keywords: Water quality in the hamlet Walannae Kampiri for parameters MPN Coliform, TSS , temperature, pH, BOD, COD